Devil´s claw: action on the central nervous system - de Lima, Valtieri Bortoluzzi; Ribeiro, Mariana Fernandes; Carpilovsky, Cristiane Köhler; Carpilovsky, Paula Köhler; Krause, Luciana Maria Fontanari (Disciplinarum Scientia | Saúde, 2021)
The Harpagophytum procumbens (HP), popularly known as “garra do diabo” is a native plant from Africa that has been used for years by traditional medicine for treating a various number of health conditions, among which the inflammatory disturbances stand out. The potential anti-inflammatory and antioxidant effects of the plant stand out since it has in its chemical matrix several bioactive compounds. However, there’s still little research that reports the association of HP on the central nervous system (CNS). The objective of this paper was to perform a review of the literature among the assays already described in the literature, in Portuguese and English, using the HP associated with the prevention and treatments of neurological and/or neuropsychiatry disturbances and conditions. The methodology performed is a review of the literature bringing publishes of papers found in the virtual database PubMed, using the descriptors: Harpagophytum procumbens (HP) and Central Nervous System (CNS). In total, 11 articles reported the effects of HP with performance on the CNS. In conclusion, this study reported, in association with previous ones, that the antioxidant action of the HP may be related to neuroprotective results due to a synergism of phenolic glycosylated derivatives such as verbascoside and/or iridoid glycosides such as harpagoside and flavonoids.